My Parents, My Grandparents Went Through Residential School, and All this Abuse has Come From it: Examining Intimate Partner Violence Against Canadian Indigenous Women in the Context of Colonialism - Ogden, Cindy (Journal of interpersonal violence, 2023)
While the global rates of intimate partner violence (IPV) for Indigenous women have been acknowledged as substantial, few studies have incorporated an analysis of the impacts of colonization in the context of IPV. This secondary mixed-methods analysis explored the experiences of 40 Indigenous women from the Canadian prairie provinces who were abused by their intimate partners. The women discussed the impact of colonization, including the use of residential schools, to break down family life, spiritual beliefs, and languages, at times linking this to IPV. Of the 40 women, 38 described male partners as the abusers and two identified female abusive partners. Consistent with the literature, many of the male partners physically assaulted the respondents so severely that the women were injured and were at risk of death. Almost half of the men (47.4%) used sexually coercive strategies and/or sexually assaulted the women. Implications include the importance of professionals considering the broader historical experiences and possible trauma of Indigenous women who seek assistance for IPV from abusive partners.